Glass window film and preparation method thereof

By using a combination technology of modified acrylate emulsion and functionalized graphene nanosheets in the glass window film, the problem of insufficient water resistance of traditional glass window films is solved, significantly improving its 180° peel strength and water resistance, and extending its use life.

CN119432253AInactive Publication Date: 2025-02-14众联晟通(苏州)科技有限公司
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510045933.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When used in areas with rainy and high humidity, traditional glass window films have poor water resistance, resulting in a significant reduction in service life.

Method used

A pressure-sensitive adhesive layer obtained by thermally curing of a modified acrylate emulsion was used to form a glass window film. This method improves the 180° peel strength and water resistance of the window film by preparing a modified acrylate emulsion and functionalized treatment of graphene nanosheets.

Benefits of technology

It significantly improves the 180° peel strength and water resistance of the glass window film, and extends the service life, especially in environments with heavy rain and high humidity.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of film materials, in particular to a glass window film and a preparation method thereof. The glass window film sequentially comprises a base material layer, a pressure-sensitive adhesive layer and a release layer from top to bottom, the pressure-sensitive adhesive layer is obtained by coating the surface of the release film with modified acrylate emulsion and then carrying out thermocuring; the base material is a polyester PET (Polyethylene Terephthalate) film, and the release film is a polyethylene glycol terephthalate film. The glass window film has excellent bonding performance and excellent water resistance, after the glass window film is soaked in water for 24 h, the water absorption rate of the glass window film does not exceed 5.7%, the water white recovery time of the glass window film after the glass window film is soaked in water for 24 h does not exceed 150 min, and the glass window film can be well suitable for areas with cloudy and rainy days and high humidity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of film materials, and in particular to a glass window film and a preparation method thereof. Background Art

[0002] Glass window film, also known as solar film, light control film, and according to its function, it is also called automobile film, architectural film, safety film, etc. It is a multi-layer functional PET polyester composite film material with super toughness, which can alleviate the defects of low flexural strength and easy breakage of glass under impact, greatly improve the impact resistance of glass, and avoid personal injury accidents caused by glass shattering and falling off, and fragments splashing; at the same time, it has protection and anti-theft functions. In addition, window film attached to the glass surface can also play the role of heat preservation, heat insulation, energy saving, UV protection, beautification of appearance and privacy shielding.

[0003] Patent document CN110205041A discloses a carrier-free window film and a glass window. The carrier-free window film includes an anti-scratch layer and a pressure-sensitive adhesive layer connected in sequence. The carrier-free window film reduces the substrate layer, but ensures that the window film also has good mechanical properties and bonding properties. At the same time, reducing the substrate layer can reduce the production cost of the carrier-free window film. Patent document CN104149453B discloses a UV-blocking window film. The invention is composed of an anti-scratch layer, a polyester film or polyethylene film substrate, a UV-blocking pressure-sensitive adhesive layer and a release film, and each layer is composited into one. The window film of the invention can block ultraviolet rays for a long time.

[0004] However, in actual use in rainy and humid areas, the service life of the window film is often greatly reduced due to its poor water resistance. Summary of the invention

[0005] In view of this, an object of the present invention is to provide a glass window film and a preparation method thereof to solve the problem that the conventional glass window film has poor water resistance.

[0006] Based on the above purpose, the present invention provides a glass window film, which comprises a substrate layer, a pressure-sensitive adhesive layer and a release layer from top to bottom; the pressure-sensitive adhesive layer is obtained by coating a modified acrylic emulsion on the surface of the release film and then thermally curing; The preparation steps of the modified acrylic emulsion are as follows: The emulsifier and deionized water are mixed and stirred evenly, and then methyl methacrylate, n-butyl acrylate, isooctyl acrylate, ethyl acrylate, acrylic acid, hydroxyethyl acrylate and modified graphene nanosheets are added to the reaction system, and stirred for 15-30 minutes to obtain a pre-emulsion; the deionized water and the initiator are mixed, heated and stirred evenly, and when the temperature reaches 85-90°C, the pre-emulsion and the initiator are added dropwise to the reaction system, reacted for 4-5 hours, kept warm for 0.5 hours, and then ammonia water is added, the pH is adjusted to 5-6, and filtered to obtain a modified acrylate emulsion; The preparation steps of the modified graphene nanosheets are as follows: S1: dispersing graphene oxide in deionized water, ultrasonically treating, adding hydrazine hydrate, reacting at 100°C for 20-24 h, filtering, washing, and drying to obtain graphene nanosheets; Preferably, the concentration of hydrazine hydrate in step S1 is 65%.

[0007] S2: Dispersing graphene nanosheets in N,N-dimethylformamide, stirring evenly, then adding MDI and silane coupling agent KH-570, reacting for 4-5 hours at 70-75°C in a nitrogen atmosphere, filtering, washing, and drying to obtain functionalized graphene nanosheets; Preferably, the washing in step S2 is performed using DMF, the purpose of which is to remove unreacted MDI.

[0008] S3: placing allyl 2-ethylhexanoate in tetrahydrofuran, adding TEMPO and CuBr2, reacting for 4-6 hours at 40-50°C in an oxygen atmosphere, filtering and purifying to obtain a modified substance; S4: Disperse the functionalized graphene nanosheets in chloroform, perform ultrasonic vibration, then add the modified substance, stir evenly, and then add triethylamine. React for 4-5 hours at 40-45°C in a nitrogen atmosphere, precipitate, filter, wash, and dry to obtain the modified graphene nanosheets.

[0009] Preferably, the precipitation in step S4 is carried out in acetone.

[0010] Preferably, the drying in step S4 is carried out in a vacuum oven at 100-120° C. for 12 hours.

[0011] Preferably, the substrate is a polyester PET film.

[0012] Preferably, the release film is a polyethylene terephthalate film.

[0013] Preferably, the usage ratio of methyl methacrylate, n-butyl acrylate, isooctyl acrylate, ethyl acrylate, acrylic acid, hydroxyethyl acrylate, modified graphene nanosheets, emulsifier, initiator and deionized water is 70-80g:280-320g:80-120g:20-30g:3-4g:3-4g:2-3g:5-6g:2-3g:250-300g.

[0014] Preferably, the emulsifier is a mixture of CM-30 and DES-30 in a weight ratio of 4:1, and the initiator is ammonium persulfate.

[0015] Preferably, in step S1, the usage ratio of graphene oxide, hydrazine hydrate and deionized water is 2.4-3 g:0.8-1 ml:500-800 ml.

[0016] Preferably, in step S2, the usage ratio of the graphene nanosheets, MDI, silane coupling agent KH-570, and N,N-dimethylformamide is 2-3 g: 5-10 g: 15-20 g: 700-800 ml.

[0017] Preferably, the weight ratio of allyl 2-ethylhexanoate, TEMPO, CuBr2 and tetrahydrofuran in step S3 is 20-30g:0.1g:0.05g:500-700g.

[0018] Preferably, in step S4, the weight ratio of the functionalized graphene nanosheets, the modified substance, triethylamine and chloroform is 2-3 g: 20-30 g: 1-2 g: 200-300 g.

[0019] Furthermore, the present invention also provides a method for preparing a glass window film, and the specific steps are as follows: uniformly coating the modified acrylic ester emulsion on the release film, and then drying it in an oven at 100°C, then taking it out and covering the adhesive surface with a polyester PET film, and curing it in an environment of 25°C and a relative humidity of 50% for 24 hours to obtain a glass window film.

[0020] Preferably, the coating is performed using a 50 μm wire rod.

[0021] Preferably, the coating has a thickness of 15-20 μm.

[0022] Beneficial effects of the present invention: The glass window film of the present invention uses a pressure-sensitive adhesive layer obtained by curing a modified acrylic ester emulsion, so that the 180° peeling strength and water resistance of the glass window film are significantly improved.

[0023] The glass window film of the present invention introduces inorganic particles and large side groups by adding graphene nanosheets and allyl 2-ethylhexanoate into the reaction system, so that the 180° peeling strength and water resistance of the final glass window film are significantly improved.

[0024] The glass window film of the present invention is prepared by first grafting allyl 2-ethylhexanoate onto the surface of graphene nanosheets and then grafting the modified graphene nanosheets into a polymer network. Compared with grafting allyl 2-ethylhexanoate and double-bonded graphene nanosheets into a polymer network, the graphene nanosheets and allyl 2-ethylhexanoate have a synergistic effect through the grafting method, so that the 180° peel strength and water resistance of the glass window film are finally significantly improved. DETAILED DESCRIPTION

[0025] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0026] The emulsifier used in the examples and comparative examples of the present invention is a mixture of CM-30 and DES-30 in a weight ratio of 4:1.

[0027] Embodiment 1: A glass window film, the specific preparation steps are as follows: (1) 2.4 g of graphene oxide was dispersed in 500 ml of deionized water and subjected to ultrasonic treatment until the solution turned into a transparent yellow-brown color. Then, 0.8 ml of hydrazine hydrate solution (65%) was added while stirring. The mixture was reacted in an oil bath at 100 °C for 20 h. The mixture was filtered and washed. The obtained product was then dried in a vacuum oven for 24 h to obtain graphene nanosheets. (2) 2 g of graphene nanosheets were dispersed in 700 ml of N,N-dimethylformamide, and then 5 g of MDI and 15 g of silane coupling agent KH-570 were added to the reaction system after ultrasonic homogenization. The mixture was reacted at 70 °C in a nitrogen atmosphere for 4 h, filtered, washed with DMF, and then dried in a vacuum oven for 10 h to obtain functionalized graphene nanosheets. (3) 20 g of allyl 2-ethylhexanoate was placed in 500 g of tetrahydrofuran, 0.1 g of TEMPO and 0.05 g of CuBr2 were added, and the mixture was reacted at 40°C in an oxygen atmosphere for 4 h, filtered, and purified to obtain a modified substance; (4) Disperse 2 g of functionalized graphene nanosheets in 200 g of chloroform, and then add 20 g of the modified substance to the reaction system after ultrasonic homogenization. Then add 1 g of triethylamine and react for 4 h at 40 °C in a nitrogen atmosphere. After the reaction is completed, precipitate in excess acetone, filter, wash, and dry the resulting powder in a vacuum oven at 100 °C for 12 h to obtain modified graphene nanosheets. (5) 4 g of emulsifier and 125 g of deionized water were mixed and stirred evenly, and then 70 g of methyl methacrylate, 280 g of n-butyl acrylate, 80 g of isooctyl acrylate, 20 g of ethyl acrylate, 3 g of acrylic acid, 3 g of hydroxyethyl acrylate and 2 g of modified graphene nanosheets were added to the reaction system and stirred for 15 min to obtain a pre-emulsion; 125 g of water was mixed with 1.5 g of ammonium persulfate, heated and stirred evenly, and when the temperature reached 85 °C, the pre-emulsion and 0.5 g of ammonium persulfate were added dropwise to the reaction system, reacted for 4 h, kept warm for 0.5 h, and then ammonia water was added to adjust the pH to 5, filtered, and a modified acrylic ester emulsion was obtained; (6) Place the modified acrylic emulsion on the release film and use a 50 μm wire rod to evenly coat the emulsion on the release film. Then quickly put it into a 100 °C oven for drying. Take it out after 4 min and cover the adhesive surface with a biaxially oriented polyester PET film. Curing the pressure-sensitive adhesive sample at 25 °C and 50% relative humidity for 24 h, a glass window film with a thickness of 20 μm can be obtained.

[0028] Embodiment 2: A glass window film, the specific preparation steps are as follows: (1) 2.47 g of graphene oxide was dispersed in 700 ml of deionized water and subjected to ultrasonic treatment until the solution turned into a transparent yellow-brown color. Subsequently, 0.9 ml of hydrazine hydrate solution (65%) was added while stirring. The mixture was reacted in an oil bath at 100 °C for 22 h. The mixture was filtered and washed. The resulting product was then dried in a vacuum oven for 24 h to obtain graphene nanosheets. (2) Dispersing 2.5 g of graphene nanosheets in 750 ml of N,N-dimethylformamide, and then adding 7.5 g of MDI and 17.5 g of silane coupling agent KH-570 to the reaction system after ultrasonic homogenization, reacting for 5 h at 73 ° C in a nitrogen atmosphere, filtering, washing with DMF, and then drying in a vacuum oven for 10 h to obtain functionalized graphene nanosheets; (3) 25 g of allyl 2-ethylhexanoate was placed in 600 g of tetrahydrofuran, 0.1 g of TEMPO and 0.05 g of CuBr2 were added, and the mixture was reacted at 45 °C in an oxygen atmosphere for 5 h. The mixture was filtered and purified to obtain a modified substance. (4) Disperse 2.5 g of functionalized graphene nanosheets in 250 g of chloroform, and then add 25 g of the modified substance to the reaction system after ultrasonic homogenization. Then add 1.5 g of triethylamine and react for 4 h at 43 °C in a nitrogen atmosphere. After the reaction is completed, precipitate in excess acetone, filter, wash, and dry the resulting powder in a vacuum oven at 110 °C for 12 h to obtain modified graphene nanosheets. (5) 4.5 g of emulsifier and 140 g of deionized water were mixed and stirred evenly, and then 75 g of methyl methacrylate, 300 g of n-butyl acrylate, 100 g of isooctyl acrylate, 25 g of ethyl acrylate, 3.5 g of acrylic acid, 3.5 g of hydroxyethyl acrylate and 2.5 g of modified graphene nanosheets were added to the reaction system and stirred for 25 min to obtain a pre-emulsion; 140 g of water was mixed with 1.8 g of ammonium persulfate, heated and stirred evenly, and when the temperature reached 90 ° C, the pre-emulsion and 0.8 g of ammonium persulfate were added dropwise to the reaction system, reacted for 5 h, kept warm for 0.5 h, and then ammonia water was added to adjust the pH to 5.7, filtered, and a modified acrylic ester emulsion was obtained; (6) Place the modified acrylic emulsion on the release film and use a 50 μm wire rod to evenly coat the emulsion on the release film. Then quickly put it into a 100 °C oven for drying. Take it out after 4 min and cover the adhesive surface with a biaxially oriented polyester PET film. Curing the pressure-sensitive adhesive sample at 25 °C and 50% relative humidity for 24 h, a glass window film with a thickness of 20 μm can be obtained.

[0029] Embodiment 3: A glass window film, the specific preparation steps are as follows: (1) 3 g of graphene oxide was dispersed in 800 ml of deionized water and subjected to ultrasonic treatment until the solution turned into a transparent yellow-brown color. Then, 1 ml of hydrazine hydrate solution (65%) was added while stirring. The mixture was reacted in an oil bath at 100 °C for 24 h. The mixture was filtered and washed. The obtained product was then dried in a vacuum oven for 24 h to obtain graphene nanosheets. (2) 3 g of graphene nanosheets were dispersed in 800 ml of N,N-dimethylformamide, and then 10 g of MDI and 20 g of silane coupling agent KH-570 were added to the reaction system after ultrasonic homogenization. The mixture was reacted at 75 °C in a nitrogen atmosphere for 5 h, filtered, washed with DMF, and then dried in a vacuum oven for 10 h to obtain functionalized graphene nanosheets. (3) 30 g of allyl 2-ethylhexanoate was placed in 700 g of tetrahydrofuran, 0.1 g of TEMPO and 0.05 g of CuBr2 were added, and the mixture was reacted in an oxygen atmosphere at 40-50° C. for 6 h, filtered, and purified to obtain a modified substance; (4) Dispersing 3 g of functionalized graphene nanosheets in 300 g of chloroform, ultrasonically homogenizing, then adding 30 g of modified substance into the reaction system, stirring evenly, adding 2 g of triethylamine, reacting for 5 h at 45 °C in a nitrogen atmosphere, and after the reaction is completed, precipitating in excess acetone, filtering, washing, and drying the obtained powder in a vacuum oven at 120 °C for 12 h to obtain modified graphene nanosheets; (5) 5 g of emulsifier and 150 g of deionized water were mixed and stirred evenly, and then 80 g of methyl methacrylate, 320 g of n-butyl acrylate, 120 g of isooctyl acrylate, 30 g of ethyl acrylate, 4 g of acrylic acid, 4 g of hydroxyethyl acrylate and 3 g of modified graphene nanosheets were added to the reaction system and stirred for 30 min to obtain a pre-emulsion; 150 g of water was mixed with 2 g of ammonium persulfate, heated and stirred evenly, and when the temperature reached 90 °C, the pre-emulsion and 1 g of ammonium persulfate were added dropwise to the reaction system, reacted for 5 h, kept warm for 0.5 h, and then ammonia water was added to adjust the pH to 6, filtered, and a modified acrylic ester emulsion was obtained; (6) Place the modified acrylic emulsion on the release film and use a 50 μm wire rod to evenly coat the emulsion on the release film. Then quickly put it into a 100 °C oven for drying. Take it out after 4 min and cover the adhesive surface with a biaxially oriented polyester PET film. Curing the pressure-sensitive adhesive sample at 25 °C and 50% relative humidity for 24 h, a glass window film with a thickness of 20 μm can be obtained.

[0030] Comparative Example 1: A glass window film, the specific preparation steps are as follows: (1) 2.47 g of graphene oxide was dispersed in 700 ml of deionized water and subjected to ultrasonic treatment until the solution turned into a transparent yellow-brown color. Subsequently, 0.9 ml of hydrazine hydrate solution (65%) was added while stirring. The mixture was reacted in an oil bath at 100 °C for 22 h. The mixture was filtered and washed. The resulting product was then dried in a vacuum oven for 24 h to obtain graphene nanosheets. (2) 2.5 g of graphene nanosheets were dispersed in 750 ml of N,N-dimethylformamide, and then 17.5 g of silane coupling agent KH-570 was added to the reaction system after ultrasonic homogenization. The mixture was reacted at 73 °C for 5 h, filtered, washed, and then dried in a vacuum oven for 10 h to obtain double-bonded graphene nanosheets. (3) 4.5 g of emulsifier and 140 g of deionized water were mixed and stirred evenly, and then 75 g of methyl methacrylate, 300 g of n-butyl acrylate, 100 g of isooctyl acrylate, 25 g of ethyl acrylate, 3.5 g of acrylic acid, 3.5 g of hydroxyethyl acrylate, 1.25 g of double-bonded graphene nanosheets and 1.25 g of allyl 2-ethylhexanoate were added to the reaction system and stirred for 25 min to obtain a pre-emulsion; 140 g of water and 1.8 g of ammonium persulfate were mixed, heated and stirred evenly, and when the temperature reached 90 ° C, the pre-emulsion and 0.8 g of ammonium persulfate were added dropwise to the reaction system, reacted for 5 h, kept warm for 0.5 h, and then ammonia water was added to adjust the pH to 5.7, filtered, and a modified acrylic emulsion was obtained; (4) Place the modified acrylic emulsion on the release film and use a 50 μm wire rod to evenly coat the emulsion on the release film. Then quickly put it into a 100 °C oven for drying. Take it out after 4 min and cover the adhesive surface with a biaxially oriented polyester PET film. Curing the pressure-sensitive adhesive sample at 25 °C and 50% relative humidity for 24 h, a glass window film with a thickness of 20 μm can be obtained.

[0031] Comparative Example 2: A glass window film, the specific preparation steps are as follows: (1) 2.47 g of graphene oxide was dispersed in 700 ml of deionized water and subjected to ultrasonic treatment until the solution turned into a transparent yellow-brown color. Subsequently, 0.9 ml of hydrazine hydrate solution (65%) was added while stirring. The mixture was reacted in an oil bath at 100 °C for 22 h. The mixture was filtered and washed. The resulting product was then dried in a vacuum oven for 24 h to obtain graphene nanosheets. (2) 4.5 g of emulsifier and 140 g of deionized water were mixed and stirred evenly, and then 75 g of methyl methacrylate, 300 g of n-butyl acrylate, 100 g of isooctyl acrylate, 25 g of ethyl acrylate, 3.5 g of acrylic acid, 3.5 g of hydroxyethyl acrylate, 1.25 g of graphene nanosheets and 1.25 g of allyl 2-ethylhexanoate were added to the reaction system and stirred for 25 min to obtain a pre-emulsion; 140 g of water and 1.8 g of ammonium persulfate were mixed, heated and stirred evenly, and when the temperature reached 90°C, the pre-emulsion and 0.8 g of ammonium persulfate were added dropwise to the reaction system, reacted for 5 h, kept warm for 0.5 h, and then ammonia water was added to adjust the pH to 5.7, filtered, and a modified acrylic emulsion was obtained; (3) Place the modified acrylic emulsion on the release film and use a 50 μm wire rod to evenly coat the emulsion on the release film. Then quickly put it into a 100 °C oven for drying. Take it out after 4 min and cover the adhesive surface with a biaxially oriented polyester PET film. Curing the pressure-sensitive adhesive sample at 25 °C and 50% relative humidity for 24 h, a glass window film with a thickness of 20 μm can be obtained.

[0032] Comparative Example 3: A glass window film, the specific preparation steps are as follows: (1) 4.5 g of emulsifier and 140 g of deionized water were mixed and stirred evenly, and then 75 g of methyl methacrylate, 300 g of n-butyl acrylate, 100 g of isooctyl acrylate, 25 g of ethyl acrylate, 3.5 g of acrylic acid, and 3.5 g of hydroxyethyl acrylate were added to the reaction system and stirred for 25 min to obtain a pre-emulsion; 140 g of water was mixed with 1.8 g of ammonium persulfate, heated and stirred evenly, and when the temperature reached 90°C, the pre-emulsion and 0.8 g of ammonium persulfate were added dropwise to the reaction system, reacted for 5 h, kept warm for 0.5 h, and then ammonia water was added to adjust the pH to 5.7, filtered, and a modified acrylate emulsion was obtained; (2) Place the modified acrylic emulsion on the release film and use a 50 μm wire rod to evenly coat the emulsion on the release film. Then quickly put it into a 100 °C oven for drying. Take it out after 4 min and cover the adhesive surface with a biaxially oriented polyester PET film. Curing the pressure-sensitive adhesive sample at 25 °C and 50% relative humidity for 24 h, a glass window film with a thickness of 20 μm can be obtained.

[0033] Performance Testing The samples obtained in the examples and comparative examples were cut into 25 mm × 175 mm sample strips using a sample cutter, and performance tests were performed on them: Initial adhesion: The circular initial adhesion of the pressure-sensitive adhesive tape was measured using a circular initial adhesion tester according to GB / T 31125-2014. The test results are shown in Table 1. 180° peel strength: The sample strip was pasted on a 50 mm × 250 mm glass plate and rolled back and forth three times using a 2 kg roller. The sample strip was cured for 20 min in a constant temperature and humidity environment, and then a 180° peel strength test was performed using an electronic tensile testing machine. The test results are shown in Table 1. Water absorption rate: 10 g of the obtained emulsion sample was placed on a watch glass and placed in a constant temperature oven at 60 °C for 48 h for drying. The film was then cut into samples of 40 mm × 40 mm, and the film thickness was controlled to be about 2 mm. The mass of the film at this time was weighed as m0. The film was then placed in deionized water, and the water surface was ensured to be completely immersed in the film. After 24 h, the film was taken out and the surface water was completely absorbed with filter paper. The current film mass was measured as m. 1。 The water absorption rate is calculated as follows: ×100% Water whitening recovery test: 3 ml of the obtained emulsion was absorbed onto a glass plate, and the emulsion was coated into a thin film using a 100 μm wire rod. The glass plate was then placed in a constant temperature and humidity environment to form a film and cured for 24 h. The glass plate was then placed in a water tank and taken out after soaking for 24 h. The light transmittance of the film was measured using a haze tester until the film completely recovered to colorless transparency, and the time required for the final recovery was recorded. The test results are shown in Table 1.

[0034] Table 1 Performance test results <![CDATA[Initial adhesion force (N·25mm -1 )]]> <![CDATA[180° peel strength (N·25mm -1 )]]> Water absorption rate (24h) (%) Water whitening recovery time (min) Example 1 12.5 8.9 5.7 150 Example 2 12.8 8.8 5.3 146 Example 3 12.9 8.7 5.6 147 Comparative Example 1 10.3 8.2 6.6 176 Comparative Example 2 9.4 7.8 8.2 203 Comparative Example 3 13.3 7.5 9.7 267 Data Analysis: It can be seen from the data of Example 2 and Comparative Example 3 in Table 1 that the present invention slightly decreases its initial adhesion by adding graphene nanosheets and allyl 2-ethylhexanoate to the reaction system, which is mainly due to the fact that allyl 2-ethylhexanoate has a larger side group and the introduction of inorganic particles causes the flexibility of the molecular chain to decrease slightly; and the peel strength and water resistance are significantly improved, which is mainly because on the one hand allyl 2-ethylhexanoate has a plurality of end groups, and due to the strong activity of the end groups and the introduction of the inorganic filler graphene nanosheets, under strong shear force, the molecular chain can absorb more energy, thereby showing an improvement in 180° peel strength, and on the other hand, the graphene nanosheets can serve as a physical barrier, and allyl 2-ethylhexanoate has a plurality of end groups that are all hydrophobic groups, which together greatly improve the water resistance of the pressure-sensitive adhesive.

[0035] It can be seen from the data of Example 2 and Comparative Examples 1 and 2 in Table 1 that the present invention grafts allyl 2-ethylhexanoate onto the surface of graphene nanosheets first and then grafts the modified graphene nanosheets into the polymer network. Compared with grafting allyl 2-ethylhexanoate and double-bonded graphene nanosheets into the polymer network, the peel strength and water resistance are further improved. This is mainly due to the fact that the grafted graphene nanosheets can exist in the polymer network, providing good interface bonding force and optimizing the cross-linked structure. At the same time, the grafted graphene nanosheets enable the graphene nanosheets and allyl 2-ethylhexanoate to have a synergistic effect, so that a more effective physical waterproof barrier exists inside the polymer network, which hinders the penetration of water and reduces the risk of structural changes caused by moisture absorption, thereby maintaining a low water absorption rate and a short water whitening time.

[0036] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A glass window film, characterized in that: It includes a substrate layer, a pressure-sensitive adhesive layer and a release layer from top to bottom; the pressure-sensitive adhesive layer is obtained by coating a modified acrylic emulsion on the surface of the release film and then thermally curing it; The preparation steps of the modified acrylate emulsion are as follows: The emulsifier and deionized water are mixed and stirred evenly, and then methyl methacrylate, n-butyl acrylate, isooctyl acrylate, ethyl acrylate, acrylic acid, hydroxyethyl acrylate and modified graphene nanosheets are added to the reaction system, and stirred for 15-30 minutes to obtain a pre-emulsion; the deionized water and the initiator are mixed, heated and stirred evenly, and when the temperature reaches 85-90°C, the pre-emulsion and the initiator are added dropwise to the reaction system, reacted for 4-5 hours, kept warm for 0.5 hours, and then ammonia water is added, the pH is adjusted to 5-6, and filtered to obtain a modified acrylate emulsion; The preparation steps of the modified graphene nanosheets are as follows: S1: dispersing graphene oxide in deionized water, ultrasonically treating, adding hydrazine hydrate, reacting at 100°C for 20-24h, filtering, washing, and drying to obtain graphene nanosheets; S2: Dispersing graphene nanosheets in N,N-dimethylformamide, stirring evenly, then adding MDI and silane coupling agent KH-570, reacting for 4-5 hours at 70-75°C in a nitrogen atmosphere, filtering, washing, and drying to obtain functionalized graphene nanosheets; S3: placing allyl 2-ethylhexanoate in tetrahydrofuran, adding TEMPO and CuBr2, reacting in an oxygen atmosphere at 40-50°C for 4-6h, filtering and purifying to obtain a modified substance; S4: Disperse the functionalized graphene nanosheets in chloroform, perform ultrasonic vibration, then add the modified substance, stir evenly, and then add triethylamine. React for 4-5 hours at 40-45°C in a nitrogen atmosphere, precipitate, filter, wash, and dry to obtain the modified graphene nanosheets.

2. The glass window film according to claim 1, characterized in that: The substrate is a polyester PET film.

3. The glass window film according to claim 1, characterized in that: The release layer is a polyethylene terephthalate film.

4. The glass window film according to claim 1, characterized in that: The dosage ratio of the methyl methacrylate, n-butyl acrylate, isooctyl acrylate, ethyl acrylate, acrylic acid, hydroxyethyl acrylate, modified graphene nanosheets, emulsifier, initiator and deionized water is 70-80g: 280-320g: 80-120g: 20-30g: 3-4g: 3-4g: 2-3g: 5-6g: 2-3g: 250-300g.

5. The glass window film according to claim 1, characterized in that: The emulsifier is a mixture of CM-30 and DES-30 in a weight ratio of 4:1, and the initiator is ammonium persulfate.

6. The glass window film according to claim 1, characterized in that: The usage ratio of graphene oxide, hydrazine hydrate and deionized water in step S1 is 2.4-3g:0.8-1ml:500-800ml.

7. The glass window film according to claim 1, characterized in that: The usage ratio of the graphene nanosheets, MDI, silane coupling agent KH-570 and N,N-dimethylformamide in step S2 is 2-3g:5-10g:15-20g:700-800ml.

8. The glass window film according to claim 1, characterized in that: The weight ratio of allyl 2-ethylhexanoate, TEMPO, CuBr2 and tetrahydrofuran in step S3 is 20-30g:0.1g:0.05g:500-700g.

9. The glass window film according to claim 1, characterized in that: The weight ratio of the functionalized graphene nanosheets, the modified substance, triethylamine and chloroform in step S4 is 2-3 g: 20-30 g: 1-2 g: 200-300 g.

10. A method for preparing a glass window film according to any one of claims 1 to 9, characterized in that: The specific steps are as follows: evenly coat the modified acrylic emulsion on the release film, then dry it in an oven at 100°C, then take it out and cover the adhesive surface with a polyester PET film, and cure it at 25°C and 50% relative humidity for 24 hours to obtain a glass window film.

Citation Information

Patent Citations

  • UV blocking window film

    CN104149453B

  • Carrier-free window film, and glass window

    CN110205041A

  • Graphene modified waterborne acrylate resin and preparation method thereof

    CN108359047A

  • Double bond modified graphene / polyvinylidene chloride heavy-duty coating and preparation method thereof

    CN108864837A

  • Preparation method of graphene / organic fluorine-modified acrylate waterborne anticorrosive coating

    CN109439120A